Safe use of medications: learning needs and strengths for teaching mediated by virtual technologies - Figueiredo, Iolanda Gonçalves de Alencar; Pierot, Esteffany Vaz; Avelino, Fernanda Valéria Silva Dantas; Navarro, Fabiola Jazmin Caceres; Leal, Loisláyne Barros; Negreiros, Ana Luiza Barbosa (Revista de Enfermagem da UFPI, 2023)
Objective: To identify the learning needs of undergraduate nursing students about patient safety and medication safety. Methods: Descriptive and cross-sectional study, developed from March 2019 to December 2020, with a non-probabilistic and intentional sample consisting of 45 undergraduate nursing students. Data were analyzed using descriptive statistics. Results: There was a predominance of female students (73.3%) with family income between 1 and 2 minimum wages. All confirmed having access to the internet, with a daily frequency of use by participants (93.3%). The smartphone was the most used device to access the internet (77.8%), with the home being the predominant place of access (80.0%). Regarding the learning needs about patient safety and medication safety, the classification “essential” stood out among the evaluated questions. Conclusion: The main identified learning needs of the participants were: working effectively as part of a team, understanding the systems and the effect of the complexity of patient care and defining the key concepts. In addition to that, there were weaknesses in differentiating between common terms in the medication administration process.